Insight Into Whole Genome of Aeromonas veronii Isolated From Freshwater Fish by Resistome Analysis Reveal Extensively Antibiotic Resistant Traits - Sakulworakan, Rungnapa; Chokmangmeepisarn, Putita; Dinh-Hung, Nguyen; Sivaramasamy, Elayaraja; Hirono, Ikuo; Chuanchuen, Rungthip; Kayansamruaj, Pattanapon; Rodkhum, Channarong (Frontiers in Microbiology, 2021)
Aeromonas veronii outbreaks in tilapia farming caused relatively high mortality. Moreover, it was resistant to many kinds of antimicrobials used in Thailand aquaculture. According to CLSI standard, the determination of antimicrobials efficacy has been limited phenotypically and the genomics study is required. This research aimed to analyze the resistome of A. veronii isolated from diseased tilapia in Chainat, Nong Khai and Uttaradit province, Thailand. Twelve isolates of A. veronii were identified based on gyrB sequencing then the MIC values to eight antimicrobials (AMP, AML, GEN, ENR, OXO, OTC, SXT, and FFC) was determined. According to MIC patterns, whole genome sequencing (WGS) of five representatives and resistome analysis was performed, including 15 genomes of A. veronii isolated from freshwater fish available in NCBI. All tilapia isolates were susceptible to FFC but resistant to AML and AMP while OTC resistance was the most dominant. For WGS analysis, 4.5 Mbp of A. veronii was characterized, 20 ARGs were detected by resistome analysis and 16 genes were shared among A. veronii population. In conclusion, A. veronii strains isolated from tilapia exhibited resistance to several antimicrobials and multidrug resistance (MDR) which was related to the presence of multiple ARGs. Aeromonas veronii shared the ARGs in their population worldwide with possibility of plasmid-mediated acquisition according to the presence of resistance islands.